Analisis Penyusunan Laporan Keuangan Berdasarkan Standar Akuntansi Keuangan Entitas Mikro Kecil Dan Menengah (SAK EMKM) Pada Dekultur Coffee Di Kota Palembang - Ariska Aprilia; Emma Lilianti; Hendry Saladin (Universitas PGRI Palembang, 2023)
ABSTRACT This study aims to determine the application of preparation of statements of financial position, income statements, and notes to financial statements. The population of this research is the financial statements based on the Small and Medium Microfinance Accounting Standards (SAK EMKM). The sampling technique in this study is the 2021 financial statements with the criteria for Micro, Small and Medium Enterprises as stipulated in Law Number 20 of 2008 concerning MSMEs. The information analysis technique of this research uses qualitative methods. The results of this study indicate that the recording of financial reports or bookkeeping of Dekultur Espresso is still very simple and manual. Recording is done to determine cash receipts and cash disbursements based on the understanding of the owner and his employees. The results of this study indicate that the recording of financial reports in UMKM Dekultur Kopi is still not well organized and has not implemented Financial Accounting Standards according to the type of business that exists. Therefore, an understanding of accounting is needed to assist in the preparation of financial reports using the Micro, Small and Medium Entity Financial Accounting Standards. (SAK EMKM). Keywords: Financial reports, UMKM criteria and SAK EMKM. ABSTRAK Tujuan dari penelitian ini adalah untuk mengetahui bagaimana penyusunan laporan laba rugi, laporan posisi keuangan, dan catatan atas laporan keuangan diterapkan. Populasi penelitian ini adalah laporan keuangan berdasarkan Standar Akuntansi Keuangan Mikro Kecil dan Menengah (SAK EMKM). Laporan keuangan tahun 2021 yang memenuhi kriteria Usaha Mikro, Kecil, dan Menengah yang dituangkan dalam Undang-Undang Nomor 20 Tahun 2008 tentang UMKM. Pendekatan kualitatif digunakan dalam metode analisis data penelitian ini. Temuan studi ini menunjukkan bahwa proses pembukuan dan pelaporan keuangan Dekultur Coffee sebagian besar masih manual. Berdasarkan pemahaman pemilik dan karyawannya, pendapatan kas dan pengeluaran kas dicatat. Berdasarkan temuan penelitian ini, UMKM Dekultur Kopi belum menerapkan Standar Akuntansi Keuangan yang sesuai dengan jenis usaha yang dijalankannya, dan cara pencatatan laporan keuangan di sana masih belum tertata dengan rapi. Oleh karena itu, untuk membantu penyusunan laporan keuangan sesuai dengan Standar Akuntansi Keuangan Entitas Mikro, Kecil, dan Menengah diperlukan pemahaman tentang akuntansi. (SAK EMKM). Kata kunci: Laporan keuangan, kriteria UMKM dan SAK EMKM.